Quantum memories and large-scale quantum coherence based on Raman interactions - Nunn, J; Sprague, MR; Michelberger, P; Champion, T; Jin, X; Langford, N; Sussman, B; England, D; Barbieri, M; Kolthammer, W; Walmsley, I; IEEE (2013)
Applied research into quantum technologies and fundamental research into the foundations of quantum mechanics run hand in hand, since our understanding of quantum correlations both advances, and is advanced by, our ability to control large quantum systems. The off-resonant Raman interaction of light with material systems provides a powerful tool both for quantum information processing, and for accessing macroscopic non-classical states of matter. We describe a recent demonstration of entanglement between the motion of separated diamond crystals at room temperature, and the implementation of quantum memories in cesium vapour that can store and retrieve photons on demand with a time-bandwidth product exceeding 2000, both based on Raman scattering. © 2013 IEEE.